Methodological approaches for nanotoxicology using cnidarian models. (March 2013) - Ambrosone, Alfredo; Tortiglione, Claudia
Abstract The remarkable amenability of aquatic invertebrates to laboratory manipulation has already made a few species belonging to the phylum Cnidaria as attracting systems for exploring animal development. The proliferation of molecular and genomic tools, including the whole genomic sequence of the freshwater polyp Hydra vulgaris and the starlet sea anemone Nematostella vectensis, further enhances the promise of these species to investigate the evolution of key aspects of development biology. In addition, the facility with which cnidarian population can be investigated within their natural ecological context suggests that these models may be profitably expanded to address important questions in ecology and toxicology. In this review, we explore the traits that make Hydra and Nematostella exceptionally attractive model organisms in context of nanotoxicology, and highlight a number of methods and developments likely to further increase that utility in the near future.